Comparative Pedagogical Analysis of Professional Training of Specialists of Customs Service at Higher Education Institutions of the Republic of Poland and Ukraine - Tetiana Korzhynska (Pedagogical Discourse, 2016)
In the article the author makes a comparative pedagogical analysis of the professional training of specialists of customs service at higher education institutions in the Republic of Poland and Ukraine. The analysis of educational documents of higher education institutions of the Republic of Poland has allowed to analyze the syllabus of different higher education institutions that train specialists of the same specialty. The criteria under which the comparison of curricula of some higher education institutions in the Republic of Poland are identified, including the characteristics of disciplines, its quantity, the number of teaching hours, the relationship between the types of training, the specificity of training curricula. The article is devoted to the problem of professional practical training of students of specialties that allow them to perform professional customs activity. The article outlines that the comparative pedagogical analysis of the experience with regard to the professional training of future customs officers in highly developed countries, particularly in the Republic of Poland, will contribute to improving the professional training of such specialists in Ukraine. The possibility of using positive pedagogical experience of higher educational institutions of the Republic of Poland in the field of professional training of future customs officers in the national higher education system has been studied.Key words: customs service specialists, professional training, comparative pedagogical analysis, curriculum, specialty, the Republiс of Poland.